2015
DOI: 10.3892/or.2015.3786
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein suppresses 17-β-estradiol-induced migration, adhesion and invasion of breast cancer cells via the G protein-coupled receptor 30 signaling pathway

Abstract: Flavonoids are structurally similar to steroid hormones, particularly estrogens, and therefore have been studied for their potential effects on hormone-dependent cancers. Baicalein is the primary flavonoid derived from the root of Scutellaria baicalensis Georgi. In the present study, we investigated the effects of baicalein on 17β-estradiol (E2)-induced migration, adhesion and invasion of MCF-7 and SK-BR-3 breast cancer cells. The results demonstrated that baicalein suppressed E2-stimulated wound-healing migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 40 publications
2
37
0
Order By: Relevance
“…It has been well established that sustained exposure to E2 increases the risk of breast cancer (21), and inhibition of E2-mediated signaling has been suggested as a key strategy for the treatment of estrogen-dependent breast cancer (22,23). In the present study, it was demonstrated that treatment with E2 significantly enhanced the viability, migration and invasion of ERα-positive breast cancer cells.…”
Section: Discussionsupporting
confidence: 50%
“…It has been well established that sustained exposure to E2 increases the risk of breast cancer (21), and inhibition of E2-mediated signaling has been suggested as a key strategy for the treatment of estrogen-dependent breast cancer (22,23). In the present study, it was demonstrated that treatment with E2 significantly enhanced the viability, migration and invasion of ERα-positive breast cancer cells.…”
Section: Discussionsupporting
confidence: 50%
“…These investigations propose that baicalein exerts anti-estrogenic activity and inhibitory effects on ERα transcriptional function. Recently, the authors of the current study demonstrated that baicalein suppresses E2-promoted migration and invasion in MCF-7 (GPR30/ERα-positive) and SK-BR-3 (GPR30-positive/ERα-negative) breast cancer cells (23). Furthermore, it was revealed that baicalein significantly inhibited E2-or G1-induced GPR30 signal activation and GPR30 target genes, cysteine-rich 61, and connective tissue growth factor upregulation (23).…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have revealed that baicalein possesses antitumor activity in breast cancer and exhibits anti-estrogenic activity (20)(21)(22). In our previous study, it was demonstrated that baicalein is able to suppress E2 enhanced migration, adhesion and invasion of breast cancer cells and interferes with E2 or G-1 induced GPR30 signaling activation (23). However, whether this compound could inhibit E2 promoted MMP-9 upregulation and activation, as well as take effects via GPR30 remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it has been shown that bacailein not only has a therapeutic effect on non-tumorous diseases, such as acute liver failure and acute myocardial ischemia (11,12), but it also exerts an inhibitory effect on tumor diseases, including colorectal, prostate, liver, lung, skin, stomach and ovarian cancer (13)(14)(15)(16)(17). It has been reported that baicalein has wide -ranging potential antitumor effects in terms of: i) Restraining cell proliferation, invasion and metastasis; ii) promoting cell apoptosis; iii) completely inhibiting the cell cycle; iv) preventing tumor angiogenesis; v) inducing tumor cell differentiation; and vi) removing reactive oxygen free radicals and preventing the tumorigenesis (7,18,19 (20). Consistently with the results of a study by Xu et al (21), the proliferative activity of the MDA-MB-231 cells was decreased in a concentration-and time-dependent manner.…”
Section: Chemical Structure and Physiological Function Of Baicaleinmentioning
confidence: 99%
“…Therefore, inhibiting tumor cell migration and invasion is also an important part in the treatment of tumor metastasis. A study by Shang et al (18) revealed that the results from the wound-healing assay indicated that the migration rate decreased to 17±2% in the MCF-7 cells, and 13±4% in the SK-BR-3 cells, following treatment with 15 µmol/l baicalein for 24 h; the Matrigel-coated Transwell chamber system was used to investigate the effects of baicalein on the invasion of MCF-7 and SK-BR-3 cells. Baicalein was evidently able to suppress cellular invasion in a concentration-and time-dependent manner.…”
Section: Breast Cancer Cell Migration and Inhibition Of Invasion Indumentioning
confidence: 99%